CLADOSPORIUM TENUISSIMUM - A NEW PRODUCER OF XYLOGLUCANSPECIFIC ENDOGLUCANASE - RASHMI R; SIDDALINGAMURTHY K R (International Journal of Pharma and Bio Sciences, 2013)
Lignocellulosic material generated as agro-industrial wastes can be used as cheap and easily available substrates for the production of many industrial enzymes. A strain of Cladosporium tenuissimum, capable of producing xyloglucanase using tamarind kernel powder as the sole carbon source, was isolated from a soil sample collected near Bangalore. Viscometric analysis showed that it is an endoglucanase with very low activity towards carboxymethylcellulose, suggesting that it might be a xyloglucan-specific endoglucanase. The enzyme was extracellular and produced preferentially at alkaline pH, thus enhancing its viability for commercial applications. Apart from xyloglucanase activity, the culture filtrate showed FPase, β-glucosidase and β-galactosidase activities. As per our knowledge, this is the first report on C. tenuissimum as a producer of xyloglucanase.